IMPROVING STUDENTS SPEAKING ABILITY THROUGH REPETITION DRILL - Nurul Aini khoyimah; Nurul Khoyimah; Iman Santoso (PROJECT (Professional Journal of English Education), 2020)
Abstract The objective of this research is to know how repetition drill technique improves students speaking ability of the 7thgrade students of SMP Negeri 5 Cimahi in academic year 2018/2019. The research was conducted using the Classroom Action Research method involving 36 students as the research subjects. The data was collected using an oral and written test within three cycles of research. Students mean score in the 1st cycle (September4-5, 2018) is not obtained due to reasons. Students mean score in the 2nd cycle (September11-12, 2018) is 69,10. Students mean score in the 3rd cycle (September18-19, 2018) is 80,56. Students mean score in the 3rd cycle is more preminent than the 2nd cycle means that there is a significant improvement in students speaking ability. In conclusion, this research proved that students speaking ability could be improved through repetition drill technique. Keywords:  Speaking, ability, repetition drill